Akad Nikah Jarak Jauh: Studi Fatwa MUI Perspektif Maqasid Syari’ah - Eka Mardianingsih; Ahmad Rezy Meidina (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
Eka Mardianingsih, Fakultas Syariah dan Hukum UIN Sunan Kalijaga Yogyakarta ekamardianingsih92@gmail.com, ABSTRACT This article discusses long-distance marriage contracts using the MUI fatwa study from the maqasid sharia perspective. Marriage contracts are generally carried out in close proximity, not remotely, but in this paper we will discuss long-distance marriage contracts with a focus on MUI fatwas using literature. The findings in this study are that a marriage contract is said to be valid if the pillars and conditions of marriage are met and cannot be reduced in any way. What is meant by the unification of the